Safe medication disposal programme (SafeMedD) in collaboration with Alpro Pharmacy / Zafirah Liyana Abdullah and Dr. Gurmeet Kaur Surindar Singh - Abdullah, Zafirah Liyana; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
In Malaysia, the issue of pharmaceutical waste contaminating the water system has become increasingly prevalent, particularly in areas characterised by dense populations, extensive industrial activity, and agricultural practices. Pharmaceutical waste can be defined as drugs that can no longer be used because they are expired, unused, or for any other reason. It should be highlighted that there are currently only a few restrictions imposed on the release or disposal of these pharmaceutical wastes. Despite the presence of these substances in the aquatic system, little is known about how these pharmaceutical pollutants could potentially impact the ecosystem. In fact, scientists from all around the world are still unsure about where to draw the line when it comes to potential environmental risks.